The occurrence, behaviour and public perception of rock hyraxes, Procavia capensis, in urban areas - Naylor, Andrea Jayne (My University, 2016)
With the continuous urban expansion, assessing how some species can survive in urban environments, particularly through modifying their behaviour, is becoming increasingly important. Urban wildlife can show phenotypic (e.g. behavioural) flexibility to exploit urban areas but it is also possible that they could seek refuges that match their phylogenetic niche requirements. The public’s perceptions of these “urban” species may also influence their success within urban centres. Using the rock hyrax, Procavia capensis, in Greater Johannesburg as a model species, I assessed the flexible and niche conservative hypotheses for its occurrence in urban areas. In particular, I investigated 1) the behaviour and flight initiation distance (FID; a measure of habituation to people) of rock hyraxes in warm (February and September) and cold (June and July) months at an urban site, Meyersdal Eco Estate, south of Johannesburg; and 2) the occurrence and public perception of rock hyraxes in Greater Johannesburg. At Meyersdal Eco Estate, three colonies were identified along an approximately 2km gradient of proximity to humans, from those living in a storm-water drain and gardens to a colony situated >100m from houses. The three colonies showed differences in behavioural patterns compared to a natural population located in the Mountain Zebra National Park, Eastern Cape Province. Although behaviours such as basking, sunbathing, travelling, grooming, and vigilance did not change between the colonies, feeding behaviour was greater and FID scores were shorter in the colony closest to people, indicating greatest habituation to people compared to the colony furthest from people, which showed reduced feeding behaviour and greatest FID distance. The intermediately situated colony showed intermediate levels of feeding and FID. The behaviour of rock hyraxes was not influenced by deterrents (boa, Boa constrictor constrictor, dung and wild garlic, Tulbaghia violacea) used at Meyersdal to keep rock hyraxes away from gardens. Rock hyraxes ate a variety of plants including grasses, forbs, shrubs, trees and succulents at each of the colonies, but the colony closest to people also ate a variety of garden plants which I did not observe at the two other colonies, including two species of wild garlic, T. violacea and T. simmleri. Within Greater Johannesburg, rock hyraxes occurred in the northern and southern suburbs, and appeared to avoid densely urbanized areas. Resource selection functions suggested rock hyraxes associated with rocky outcrops potentially conforming to the niche conservatism hypothesis, although they did not select for any particular landscape feature in the Greater Johannesburg environment. The public viewed rock hyraxes more positively than anticipated, with most suggesting that they were part of the urban biodiversity of Greater Johannesburg. In conclusion, rock hyraxes have modified their behaviour and habituated to people over surprisingly small spatial scales. Such behavioural flexibility over comparatively short distances is a novel finding. However, rocky outcrops are still important natural habitats to meet thermoregulatory and denning requirements, and are used to explore and exploit the urban environment. Because they are constrained by their thermoregulatory requirements, habitat analogues (e.g. storm water drains) might create opportunities to enter houses and gardens. Such flexible responses, which together with a tolerant public, might allow them to flourish in Johannesburg.
Keywords: Rock hyrax.; Rock hyrax--Behaviour.; Rock hyrax--South Africa--Johannesburg.; Cities and towns--South Africa--Johannesburg.